Can Prealbumin, Albumin and CRP Levels be used to Predict Prognosis in Patients with Gastric Cancer - Enver Ilhan; Orhan Ureyen; Ugur Gökcelli (Journal of Surgery and Surgical Research - Peertechz Publications, 2016)
Background: The impact of systemic inflammatory response on carcinogenesis and tumor progression has recently gained much attention. Biochemical markers such as albumin, pre-albumin and C-reactive protein (CRP) are currently used to predict prognosis in several cancer types, and the usefulness of these biomarkers in gastric cancer has become an emerging topic of research. The present study aims to assess the correlation between tumor stage and the levels of pre-albumin, albumin and CRP in patients who underwent surgery for gastric cancer. Methods: Albumin, pre-albumin and CRP levels of the patients who underwent surgery for gastric cancer in our division, were prospectively recorded and retrospectively evaluated. Age, gender, duration of hospital stay, TNM stage, and preoperative albumin, pre-albumin and CRP levels were recorded. Albumin levels lower than 3.5 mg/dL and pre-albumin levels lower than 20 mg/dL were considered to be below the normal range. CRP levels higher than 5 mg/L were considered to be elevated. Patients with another focus of inflammation were excluded from the study. Results: A total number of 41 patients, 32 (78%) men and 9 (22%) women, were included in the study. Albumin levels were significantly associated with the age (p=0.010). There was no significant correlation between disease stage, gender, presence of metastatic lymph nodes and albumin levels (p>0.05). There was a significant correlation between the TNM stage and pre-albumin levels (P=0.014). No significant correlation was demonstrated between pre-albumin levels and the other parameters (P>0.05). The independent variables were not found to be significantly different between the groups with normal and elevated CRP levels (p>0,05). Conclusions: The present study showed that the patients with lymph node metastasis and advanced stage gastric cancer more frequently have decreased levels of albumin and pre-albumin, and elevated levels of CRP. Decreased pre-albumin level was found to be associated with the TNM stage. The albumin levels were found to be decreasing by age. Although we failed to demonstrate a statistically correlation with albumin and CRP, preoperative albumin, pre-albumin and CRP levels may be useful to predict prognosis of patients with gastric cancer.